Democratic innovations - Herranz, Cristina (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
The concept of democratic innovations has been gaining relevance in the last decade. In general, it refers to a renewed interest in involving citizens in public issues, seeking to include them in the political decision-making process. The purpose of this work is twofold. On the one hand, it seeks to delve into the development and evolution of the concept in the specialized literature, showing its theoretical background, definitions, and related concepts. On the other hand, this analysis is completed with a study of general trends in one of the most popular international databases of innovative experiences.
Keywords: Democratic innovations; citizen participation; innovation typologies; models of democracy; theories of democracy.